Numerical Algorithm for Beam Residual Stress Identification - Milan Saga; Milan Vasko; Peter Kopas; Lenka Jakubovicova (Communications - Scientific letters of the University of Zilina, 2014)
The goal of the paper is the numerical study of the original hysteresis computational material models and their application in beam’s bending theory. The paper presents the chosen differential material models and approaches based on step by step solution respecting the elastic and plastic conditions. In the centre of authors´ interest is the numerical method study of the plastic zones identification or study of residual stresses distribution in the beam’s cross-section. The results obtained from new MATLAB’s programs are compared with FEM models in ADINA.